Curriculum Revolution in Higher Education: The Mighty Role of Artificial Intelligence: Revolusi Kurikulum di Pendidikan Tinggi: Peran Dahsyat Kecerdasan Buatan - Ogunode, Niyi Jacob; UKOZOR, Conrad Ugochukwu (Indonesian Journal of Innovation Studies, 2023)
This study investigates the pivotal role of artificial intelligence (AI) in enhancing curriculum implementation within Nigerian tertiary institutions. Utilizing secondary data from diverse sources, the research underscores AI's multifaceted contributions to curriculum execution, encompassing lecture planning, instructional resource preparation, presentation, student assessment, script marking, assignment allocation, student readiness, progress monitoring, and the selection of optimal teaching methodologies. The findings emphasize the indispensable impact of AI on education. Consequently, the study advocates increased government funding for tertiary institutions and the judicious deployment of AI to harness its transformative potential in curriculum implementation on a global scale. Highlights: AI Optimization: Artificial intelligence streamlines lecture planning, resource preparation, and assessment, enhancing curriculum efficiency. Learning Enhancement: AI improves student readiness, progress monitoring, and personalized teaching methodologies. Funding Imperative: Adequate government funding is crucial to harness the full potential of AI in education. Keywords: Artificial Intelligence, Curriculum Implementation, Higher Education, Educational Technology, Government Funding